Developmental refinement of hair cell synapses tightens the coupling of Ca2+ influx to exocytosis. (18th January 2014) - Wong, Aaron B; Rutherford, Mark A; Gabrielaitis, Mantas; Pangršič, Tina; Göttfert, Fabian; Frank, Thomas; Michanski, Susann; Hell, Stefan; Wolf, Fred; Wichmann, Carolin; Moser, Tobias
Abstract Cochlear inner hair cells (IHCs) develop from pre‐sensory pacemaker to sound transducer. Here, we report that this involves changes in structure and function of the ribbon synapses between IHCs and spiral ganglion neurons (SGNs) around hearing onset in mice. As synapses matured they changed from holding several small presynaptic active zones (AZs) and apposed postsynaptic densities (PSDs) to one large AZ/PSD complex per SGN bouton. After the onset of hearing (i) IHCs had fewer and larger ribbons; (ii) CaV1.3 channels formed stripe‐like clusters rather than the smaller and round clusters at immature AZs; (iii) extrasynaptic CaV1.3‐channels were selectively reduced, (iv) the intrinsic Ca2+ dependence of fast exocytosis probed by Ca2+ uncaging remained unchanged but (v) the apparent Ca2+ dependence of exocytosis linearized, when assessed by progressive dihydropyridine block of Ca2+ influx. Biophysical modeling of exocytosis at mature and immature AZ topographies suggests that Ca2+ influx through an individual channel dominates the [Ca2+] driving exocytosis at each mature release site. We conclude that IHC synapses undergo major developmental refinements, resulting in tighter spatial coupling between Ca2+ influx and exocytosis.